Mirror Coating Research and Developments for Current and Future Gravitational‐Wave Detectors - Alex Amato; Michele Magnozzi; Janis Wöhler (Advanced Photonics Research)
In current and future gravitational‐wave detectors, thermal noise from mirror coatings limits the sensitivity of the detectors. To reduce the coating thermal noise, coatings with excellent optical and mechanical properties are needed. In this review, an overview of postdeposition coating treatments and the latest worldwide research activities on coatings with low mechanical loss and low optical absorption are reported. A brief overview of coating design optimization, including innovative solutions such as multimaterial coatings and nanolayers, is also discussed.